Biblical Review of The Church's Responsibility for Social Justice (Poverty) of Congregation Members - Herman, Samuel; Kurnia, Catherine Christianny; Lasakar, Citra Mirani; Simanjuntak, Ferry (Institut Agama Kristen Negeri Toraja, 2024)
Abstract: This study delves into the instrumental role of religious figures in tackling pressing global economic issues, particularly poverty and inequality. Employing a comprehensive literature review methodology, the research illuminates the profound impact of religious teachings on economic behaviors and scrutinizes the endeavors of religious figures in alleviating socioeconomic imbalances. The narrative is enriched with compelling examples of successful initiatives spearheaded by figures such as Mother Teresa and Abdul Sattar Edhi, underscoring the tangible positive outcomes of religious involvement. The conclusion emphatically underscores the indispensable role of religious figures in amplifying awareness, rallying support, and executing impactful social programs to forge a more equitable and prosperous societal landscape.Keywords: Economic Issues, Inequality, Poverty, Religious Figures.